Lead-free piezoelectric ceramic material with high electromechanical coupling coefficient and preparation method and application thereof
Through component regulation, ion doping and textured technology, lead-free piezoelectric ceramic materials with high electromechanical coupling coefficient were prepared, which solved the problem of poor porcelain formation in existing lead-free piezoelectric ceramic materials and achieved excellent electrical performance and the feasibility of industrial production.
Patent Information
- Application Number
- CN202411533383.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing lead-free piezoelectric ceramic materials have problems such as potassium and sodium volatility and poor porcelain formation during the ceramic preparation process, which leads to their performance not reaching the index of lead-based piezoelectric ceramics.
Component regulation, ion doping and textured technology are used to induce grains in the ceramic to grow in a certain direction by adding templates, and lead-free piezoelectric ceramic materials with high electromechanical coupling coefficient are prepared. The specific steps include weighing a specific proportion of raw materials for ball milling and drying, forming a powder base material, and then casting, drying, cutting, lamination, baking and sintering, and finally obtaining lead-free piezoelectric ceramics with excellent electrical properties. Material.
The high electromechanical coupling coefficient of lead-free piezoelectric ceramic materials is achieved, with KP reaching 57%, and d33 reaching 462 pC/N. It has the conditions for application in industry, while reducing costs, simplifying the preparation process, and avoiding the use of toxic substances. Meets the requirements of industrial production.
Smart Images

Figure CN119161184B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric ceramic materials, in particular to a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient and a preparation method and application thereof. Background Art
[0002] Piezoelectric ceramics have the property of mutual conversion between electrical energy and mechanical energy, and are widely used in various functional devices such as buzzers, atomizers, sensors and transducers. Since its invention, the Pb(Zr, Ti)O3 (PZT)-based ceramic system has dominated the field of piezoelectric applications due to its excellent electrical properties. However, lead-based piezoelectric ceramics contain a large amount of lead elements, which will cause serious harm to the environment during the preparation and disposal of ceramics. At this stage, lead-free piezoelectric materials have become the main trend of the development of piezoelectric materials.
[0003] Potassium sodium niobate-based piezoelectric ceramics can produce excellent piezoelectric properties while maintaining a high Curie temperature through phase structure regulation. They are considered to be one of the most promising piezoelectric ceramic systems to replace PZT-based ceramics. However, although potassium sodium niobate-based ceramics have excellent performance, the problems of easy volatility of potassium and sodium elements and poor ceramic forming properties during the preparation of ceramics have seriously limited their practical application. In response to the above problems, researchers systematically regulated potassium sodium niobate-based piezoelectric ceramics by means of component regulation, ion doping, and texturing processes, and prepared lead-free piezoelectric ceramic samples with good sintering characteristics and excellent performance. At present, the performance of potassium sodium niobate-based piezoelectric ceramic products at home and abroad still cannot reach the performance indicators of lead-based piezoelectric ceramics. The main reason is that the component regulation and ion doping in the formula of lead-free piezoelectric ceramics with excellent electrical properties are very fine, and the accuracy of the stoichiometric ratio of the ceramic formula cannot be guaranteed in the actual production process. The texturing process refers to inducing the grains in the ceramic to grow in a certain direction by adding a template. The sintered ceramic has anisotropy similar to that of a single crystal, and its piezoelectric performance is significantly improved. Currently, the texturing process of lead-free piezoelectric ceramics is still in the laboratory stage. There are problems such as the presence of toxic substances such as toluene in some formulas of the texturing slurry, small sample specifications and inability to prepare in batches. There is still a big gap before it can replace lead-based piezoelectric ceramics for practical applications. Summary of the invention
[0004] In view of the above shortcomings in the prior art, the purpose of the present invention is to provide a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient and excellent electrical properties, wherein the KP can reach 57%, and the d 33 It can reach 462 pC / N, so that the piezoelectric ceramic of the present invention has the conditions for application in industry.
[0005] Another object of the present invention is to provide a method for preparing a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient, which has low cost and is simple and easy to prepare and can meet the requirements of industrial production.
[0006] The third object of the present invention is to provide an application of a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient for use in energy harvesters, transducers or sensors.
[0007] The present invention is achieved by adopting the following technical solutions:
[0008] The lead-free piezoelectric ceramic material with high electromechanical coupling coefficient is prepared from the following matrix: (0.99-x)(K 0.5 Na 0.5 )(Nb 0.96 Sb 0.04 )O3-0.01BaZrO3-xBi 0.5 (Ag 0.5 Li 0.5 ) 0.5 HfO3;
[0009] In the matrix, the value of x can be one of 0.01, 0.02, 0.03 or 0.04.
[0010] The method for preparing the lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient comprises the following steps:
[0011] (1) Weighing K2CO3, Na2CO3, Nb2O5, Sb2O3, BaCO3, ZrO2, Bi2O3, Ag2O, Li2CO3, and HfO2 raw materials according to the stoichiometric ratio of the elements in the general chemical formula of the high electromechanical coupling coefficient lead-free piezoelectric ceramic material matrix, and obtaining a powder matrix after ball milling, drying, and sieving;
[0012] (2) weighing a powder base material, a NaNbO3 template, a solvent, a plasticizer, a defoamer and a binder, and mixing them by roller milling to obtain a casting slurry;
[0013] (3) casting, drying, cutting, laminating, baking, cold isostatic pressing, punching and debinding the casting slurry to obtain a ceramic green body;
[0014] (4) sintering the ceramic green body and processing the finished product into a disc with a diameter of 16 mm and a thickness of 0.7 mm to obtain a lead-free piezoelectric ceramic material;
[0015] (5) coating the lead-free piezoelectric ceramic material ceramic sheet obtained in step (4) with silver paste and sintering the ceramic sheet to obtain a piezoelectric ceramic with a silver electrode;
[0016] (6) The piezoelectric ceramic with silver electrodes obtained in step (5) is polarized to obtain a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient.
[0017] The wafers were prepared according to the national standard GB / T 2414.1-1998. In step (5), the silver paste was applied by screen printing with a thickness of 10-30 μm.
[0018] During ball milling, the weight ratio of zirconium balls to raw materials is 2:1, and the solvent is anhydrous ethanol, and the weight ratio of anhydrous ethanol to raw materials is 2-2.2:1.
[0019] The solvent in step (2) is a mixture of butyl acetate and anhydrous ethanol in a mass ratio of 1:(0.8-1.2), the plasticizer is dioctyl phthalate, the defoamer is n-butanol, and the binder is polyvinyl butyral; the mass ratio of the powder base material, NaNbO3 template, solvent, plasticizer, defoamer and binder is 10:0.3:9:0.3:0.25:0.9; and the mixing time is 10-12 hours.
[0020] During the casting in step (3), the scraper height is 100-200 μm.
[0021] The baking condition in step (3) is to increase the room temperature to 100° C. and then keep the temperature for 30-60 minutes.
[0022] The debinding conditions in step (3) are as follows: heating to 180°C at a rate of 0.5°C / min, keeping the temperature for 6 hours, then heating to 570°C at a rate of 0.2°C / min, keeping the temperature for 4 hours, and then cooling with the furnace.
[0023] The sintering conditions in step (4) are as follows: using the buried firing method, the four-component disc is heated from room temperature to 900°C at a rate of 5°C / min, then heated to 1190°C at a rate of 3°C / min, kept at that temperature for 1 minute, cooled to 1110°C at a rate of 10°C / min, kept at that temperature for 6 hours, and then cooled with the furnace.
[0024] In the step (6), the polarization temperature is 25-60° C., the polarization electric field is 15-20 kV / cm, and the polarization time is 20-30 min.
[0025] The lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient is used in energy collectors, transducers or sensors.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The lead-free piezoelectric ceramic material with high electromechanical coupling coefficient of the present invention has excellent electrical properties, and its KP can reach 57%, d 33 It can reach 462 pC / N, so that the piezoelectric ceramic of the present invention has the conditions for application in industry.
[0028] (2) The preparation process of the lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient of the present invention is safer and does not contain toxic substances such as lead and toluene.
[0029] (3) The lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient of the present invention can be prepared using industrial raw materials, has low cost and a simple and easy preparation method, and can meet the requirements of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a physical picture of the lead-free piezoelectric ceramic material with high electromechanical coupling coefficient.
[0031] Figure 2 Schematic diagram of impedance, phase angle and frequency of the lead-free piezoelectric ceramic material in Example 1.
[0032] Figure 3 Schematic diagram of impedance, phase angle and frequency of the lead-free piezoelectric ceramic material in Example 2.
[0033] Figure 4 Schematic diagram of impedance, phase angle and frequency of the lead-free piezoelectric ceramic material in Example 3.
[0034] Figure 5 Schematic diagram of impedance, phase angle and frequency of the lead-free piezoelectric ceramic material of Example 4.
[0035] Figure 6 Schematic diagram of impedance, phase angle and frequency of the lead-free piezoelectric ceramic material of comparative example 1. DETAILED DESCRIPTION
[0036] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail.
[0037] Example 1
[0038] The preparation method of lead-free piezoelectric ceramic material with high electromechanical coupling coefficient adopts the following steps:
[0039] (1) According to 0.98 (K 0.5 Na 0.5 )(Nb 0.96 Sb 0.04 )O3-0.01BaZrO3-0.01Bi 0.5 (Ag 0.5 Li 0.5 ) 0.5Weigh the dried K2CO3, Na2CO3, Nb2O5, Sb2O3, BaCO3, ZrO2, Bi2O3, Ag2O, Li2CO3 and HfO2 raw materials respectively, and the weighed raw materials total 40.51g, put them into a ball mill and add 80g of anhydrous ethanol, and mill them on a planetary ball mill for 18h, separate the milled slurry from the zirconium balls, put them into an oven and dry them at 80℃, grind the sample into powder using an agate mortar after drying, pour it into a crucible and compact it with a grinding rod, and keep it warm at 850℃ for 5h; grind the pre-burned powder into powder using an agate mortar and put it into a ball mill, add 80g of anhydrous ethanol and perform secondary ball milling for 48h, separate the milled slurry from the zirconium balls, put it into an oven and dry it at 80℃; grind the dried base material and pass it through a 200-mesh sieve to obtain a powder base material;
[0040] (2) Weigh 20 g of the powder base material, then add 0.6 g of NaNbO3 template, 18 g of solvent (the solvent is a mixture of butyl acetate and anhydrous ethanol, the mass ratio is 1:0.8), 0.6 g of dioctyl phthalate, 0.5 g of n-butanol and 1.8 g of polyvinyl butyral, and roll grind on a roller mill for 10 h at a speed of 180 r / min to obtain a casting slurry in which the binder and slurry are evenly mixed;
[0041] (3) The cast slurry is cast on the PET film by a scraper (the scraper height is 100μm). After the wet film is naturally dried, the sample film is scraped off the PET film with a blade; the scraped film is cut into square films of 2×2cm in size and stacked. The total number of film layers is maintained at 40 layers to obtain the green body before pressing. The green body is placed in an oven and heated from room temperature to 100℃ and kept warm for 30 minutes, then taken out and cold isostatically pressed (pressure is 200MPa). After taking out the pressed sample punch, the temperature is raised to 180℃ at a rate of 0.5℃ / min, kept warm for 6h, and then raised to 570℃ at a rate of 0.2℃ / min. After keeping warm for 4h, it is cooled in the furnace for debonding to obtain a ceramic green body;
[0042] (4) The green body was sintered in a muffle furnace using a two-step sintering method: from room temperature to 900°C (heating rate of 5°C / min), then heated to 1190°C at a rate of 3°C / min, kept at this temperature for 1 minute, and then rapidly cooled (cooling rate of 10°C / min) to 1110°C, and kept at this temperature for 6 hours to prepare a lead-free piezoelectric ceramic material. The sintered ceramic was processed into a disc with a diameter of 16 mm and a thickness of 0.7 mm using a grinder;
[0043] (5) After ultrasonic cleaning, the above wafers are coated with silver paste, which is applied by screen printing with a thickness of 10 μm. After silver is fired, a piezoelectric ceramic with a silver electrode is obtained;
[0044] (6) The piezoelectric ceramic with silver electrodes is polarized at a polarization temperature of 25°C, a polarization electric field of 15 kV / cm, and a polarization time of 20 min to obtain a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient. The impedance, phase angle and frequency diagram of the obtained lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient is shown in Figure 2 The actual picture of the obtained high electromechanical coupling coefficient lead-free piezoelectric ceramic material is shown in Figure 1 .
[0045] Example 2
[0046] The preparation method of lead-free piezoelectric ceramic material with high electromechanical coupling coefficient adopts the following steps:
[0047] (1) According to 0.97 (K 0.5 Na 0.5 )(Nb 0.96 Sb 0.04 )O3-0.01BaZrO3-0.02Bi 0.5 (Ag 0.5 Li 0.5 ) 0.5 Weigh the dried K2CO3, Na2CO3, Nb2O5, Sb2O3, BaCO3, ZrO2, Bi2O3, Ag2O, Li2CO3 and HfO2 raw materials respectively, and the weighed raw materials total 40.89g, put them into a ball mill and add 80g of anhydrous ethanol, and ball mill them on a planetary ball mill for 18h, separate the milled slurry from the zirconium balls and put them into an oven and dry them at 80℃, grind the sample into powder using an agate mortar after drying, pour it into a crucible and compact it with a grinding rod, and keep it warm at 850℃ for 5h; grind the pre-burned powder into powder using an agate mortar and put it into a ball mill, add 80g of anhydrous ethanol and perform secondary ball milling for 48h, separate the milled slurry from the zirconium balls and put it into an oven and dry it at 80℃; grind the dried base material and pass it through a 200-mesh sieve to obtain a powder base material;
[0048] (2) Weigh 20 g of the powder base material, then add 0.6 g of NaNbO3 template, 18 g of solvent (the solvent is a mixture of butyl acetate and anhydrous ethanol, the mass ratio is 1:1.2), 0.6 g of dioctyl phthalate, 0.5 g of n-butanol and 1.8 g of polyvinyl butyral, and then roll grind on a roller mill for 12 h at a speed of 200 r / min to obtain a casting slurry in which the binder and slurry are evenly mixed;
[0049] (3) The cast slurry is cast on the PET film by a scraper (the scraper height is 200μm). After the wet film is naturally dried, the sample film is scraped off the PET film with a blade; the scraped film is cut into square films of 2×2cm in size and stacked. The total number of film layers is maintained at 60 layers to obtain the green body before pressing. The green body is placed in an oven and heated from room temperature to 100℃ and kept at this temperature for 60 minutes. After that, it is taken out and cold isostatically pressed (pressure is 200MPa). After taking out the pressed sample punch, the temperature is raised to 180℃ at a rate of 0.5℃ / min. After keeping at this temperature for 6 hours, the temperature is raised to 570℃ at a rate of 0.2℃ / min. After keeping at this temperature for 4 hours, it is cooled in the furnace for debonding to obtain a ceramic green body.
[0050] (4) The green body was sintered in a muffle furnace using a two-step sintering method: from room temperature to 900°C (heating rate of 5°C / min), then heated to 1190°C at a rate of 3°C / min, kept at that temperature for 1 minute, and then rapidly cooled (cooling rate of 10°C / min) to 1110°C, and kept at this temperature for 6 hours to prepare a lead-free piezoelectric ceramic material. The sintered ceramic was processed into a disc with a diameter of 16 mm and a thickness of 0.7 mm using a grinder;
[0051] (5) After ultrasonic cleaning, the above wafers are coated with silver paste, which is applied by screen printing with a thickness of 30 μm. After silver is fired, a piezoelectric ceramic with a silver electrode is obtained;
[0052] (6) The piezoelectric ceramic with silver electrodes was polarized at a polarization temperature of 55°C, a polarization electric field of 20 kV / cm, and a polarization time of 30 min to obtain a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient. The impedance, phase angle and frequency diagram of the obtained lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient is shown in Figure 3 .
[0053] Example 3
[0054] The preparation method of lead-free piezoelectric ceramic material with high electromechanical coupling coefficient adopts the following steps:
[0055] (1) According to 0.96 (K 0.5 Na 0.5 )(Nb 0.96 Sb 0.04 )O3-0.01BaZrO3-0.03Bi 0.5 (Ag 0.5 Li 0.5 ) 0.5Weigh the dried K2CO3, Na2CO3, Nb2O5, Sb2O3, BaCO3, ZrO2, Bi2O3, Ag2O, Li2CO3 and HfO2 raw materials respectively, with a total weight of 41.27g, put them into a ball mill and add 80g of anhydrous ethanol, and mill them on a planetary ball mill for 18h. After separating the milled slurry from the zirconium balls, put them into an oven and dry them at 80℃. After drying, use an agate mortar to grind the sample into powder, pour it into a crucible and compact it with a grinding rod, and keep it warm at 850℃ for 5h; use an agate mortar to grind the pre-burned powder into powder and put it into a ball mill, add 80g of anhydrous ethanol and perform secondary ball milling for 48h. After separating the milled slurry from the zirconium balls, put it into an oven and dry it at 80℃; grind the dried base material and pass it through a 200-mesh sieve to obtain a powder base material;
[0056] (2) Weigh 20 g of the powder base material, then add 0.6 g of NaNbO3 template, 18 g of solvent (the solvent is a mixture of butyl acetate and anhydrous ethanol, the mass ratio is 1:1), 0.6 g of dioctyl phthalate, 0.5 g of n-butanol and 1.8 g of polyvinyl butyral, and roll grind on a roller mill for 10 h at a speed of 180-200 r / min to obtain a casting slurry in which the binder and slurry are evenly mixed;
[0057] (3) The cast slurry is cast on the PET film by a scraper (the scraper height is 160μm). After the wet film is naturally dried, the sample film is scraped off the PET film with a blade; the scraped film is cut into square films of 2×2cm in size and stacked. The total number of film layers is maintained at 50 layers to obtain the green body before pressing. The green body is placed in an oven and heated from room temperature to 100℃ and kept warm for 30 minutes. After that, it is taken out and cold isostatically pressed (pressure is 200MPa). After taking out the pressed sample punch, the temperature is raised to 180℃ at a rate of 0.5℃ / min. After keeping warm for 6 hours, the temperature is raised to 570℃ at a rate of 0.2℃ / min. After keeping warm for 4 hours, it is cooled in the furnace for debonding to obtain a ceramic green body;
[0058] (4) The green body is then sintered in a muffle furnace using a two-step sintering method: from room temperature to 900°C (heating rate of 5°C / min), then heated to 1190°C at a rate of 3°C / min, kept at this temperature for 1 minute, and then rapidly cooled (cooling rate of 10°C / min) to 1110°C, and kept at this temperature for 6 hours to prepare a lead-free piezoelectric ceramic material. The sintered ceramic is processed into a disc with a diameter of 16 mm and a thickness of 0.7 mm using a grinder;
[0059] (5) After ultrasonic cleaning, the above wafers are coated with silver paste, which is applied by screen printing with a thickness of 20 μm. After silver is fired, a piezoelectric ceramic with a silver electrode is obtained;
[0060] (6) The piezoelectric ceramic with silver electrodes is polarized at a polarization temperature of 25°C, a polarization electric field of 20 kV / cm, and a polarization time of 25 min to obtain a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient. The impedance, phase angle and frequency diagram of the obtained lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient is shown in Figure 4 .
[0061] Example 4
[0062] The preparation method of lead-free piezoelectric ceramic material with high electromechanical coupling coefficient adopts the following steps:
[0063] (1) According to 0.95 (K 0.5 Na 0.5 )(Nb 0.96 Sb 0.04 )O3-0.01BaZrO3-0.04Bi 0.5 (Ag 0.5 Li 0.5 ) 0.5 Weigh the dried K2CO3, Na2CO3, Nb2O5, Sb2O3, BaCO3, ZrO2, Bi2O3, Ag2O, Li2CO3 and HfO2 raw materials respectively, and the weighed raw materials total 41.65g, put them into a ball mill and add 80g of anhydrous ethanol, and mill them on a planetary ball mill for 18h, separate the milled slurry from the zirconium balls, put them into an oven and dry them at 80℃, grind the sample into powder using an agate mortar after drying, pour it into a crucible and compact it with a grinding rod, and keep it warm at 850℃ for 5h; grind the pre-burned powder into powder using an agate mortar and put it into a ball mill, add 80g of anhydrous ethanol and perform secondary ball milling for 48h, separate the milled slurry from the zirconium balls, put it into an oven and dry it at 80℃; grind the dried base material and pass it through a 200-mesh sieve to obtain a powder base material;
[0064] (2) Weigh 20 g of the powder base material, then add 0.6 g of NaNbO3 template, 18 g of solvent (the solvent is a mixture of butyl acetate and anhydrous ethanol, the mass ratio is 1:1), 0.6 g of dioctyl phthalate, 0.5 g of n-butanol and 1.8 g of polyvinyl butyral, and roll grind on a roller mill for 10 h at a speed of 180-200 r / min to obtain a casting slurry in which the binder and slurry are evenly mixed;
[0065] (3) The cast slurry is cast on the PET film by a scraper (the scraper height is 180μm). After the wet film is naturally dried, the sample film is scraped off the PET film with a blade; the scraped film is cut into square films of 2×2cm in size and stacked. The total number of film layers is maintained at 60 layers to obtain the green body before pressing. The green body is placed in an oven and heated from room temperature to 100℃ and kept warm for 30 minutes. After that, it is taken out and cold isostatically pressed (pressure is 200MPa). After taking out the pressed sample punch, the temperature is raised to 180℃ at a rate of 0.5℃ / min. After keeping warm for 6 hours, the temperature is raised to 570℃ at a rate of 0.2℃ / min. After keeping warm for 4 hours, it is cooled in the furnace for debonding to obtain a ceramic green body;
[0066] (4) The green body was sintered in a muffle furnace using a two-step sintering method: from room temperature to 900°C (heating rate of 5°C / min), then heated to 1190°C at a rate of 3°C / min, kept at that temperature for 1 minute, and then rapidly cooled (cooling rate of 10°C / min) to 1110°C, and kept at this temperature for 6 hours to prepare a lead-free piezoelectric ceramic material. The sintered ceramic was processed into a disc with a diameter of 16 mm and a thickness of 0.7 mm using a grinder;
[0067] (5) After ultrasonic cleaning, the above wafers are coated with silver paste, which is applied by screen printing with a thickness of 30 μm. After silver is fired, a piezoelectric ceramic with a silver electrode is obtained;
[0068] (6) The piezoelectric ceramic with silver electrodes is polarized at a polarization temperature of 45°C, a polarization electric field of 20 kV / cm, and a polarization time of 25 min to obtain a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient. The impedance, phase angle and frequency diagram of the obtained lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient is shown in Figure 5 .
[0069] Comparative Example 1
[0070] A method for preparing a lead-free piezoelectric ceramic material comprises the following steps:
[0071] The preparation method is the same as that of Example 3, except that the NaNbO3 template is not added in step (2). The impedance, phase angle and frequency diagram of the obtained lead-free piezoelectric ceramic material is shown in Figure 6 .
[0072] The test data of Examples 1-4 and Comparative Example 1 are shown in Table 1.
[0073] Table 1 Test data of Examples 1-4 and Comparative Example 1
[0074]
[0075] The electromechanical coupling coefficient KP listed in Table 1 is calculated from the resonant and anti-resonant frequencies in the attached figure, and the calculation formula is as follows:
[0076] ;
[0077] Among them, fr is the resonant frequency; fa is the anti-resonant frequency.
[0078] From the data in Table 1, it can be seen that with the continuous increase of the doping amount of the component, the piezoelectric properties of the ceramic show a trend of first increasing and then decreasing, indicating that appropriate component doping can regulate the phase structure of the ceramic at room temperature and thus affect the ceramic properties, thereby promoting the improvement of the piezoelectric properties of the ceramic. From the performance comparison between Example 3 and Comparative Example 1, it can be seen that the texturing process has a significant effect on the improvement of the piezoelectric properties of the ceramic. 33 and KP increased by 64% and 39% respectively, and the performance is better than the lead-free piezoelectric ceramics currently used to prepare buzzer sheets in the market. The present invention not only optimizes the piezoelectric performance of ceramics based on component regulation and texture technology, but also adjusts the safety (no toxic substances such as toluene and lead elements) and feasibility (low cost and simple process) of the textured ceramic preparation process, which can meet the requirements of mass production.
Claims
1. A lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient, characterized in that: Prepared from the following matrix: (0.99-x)(K 0.5 Na 0.5 )(Nb 0.96 Sb 0.04 )O3-0.01BaZrO3-xBi 0.5 (Ag 0.5 Li 0.5 ) 0.5 HfO3; In the matrix, the value of x is one of 0.01, 0.02, 0.03 or 0.04; The method for preparing the lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient comprises the following steps: (1) Weighing K2CO3, Na2CO3, Nb2O5, Sb2O3, BaCO3, ZrO2, Bi2O3, Ag2O, Li2CO3, and HfO2 raw materials according to the stoichiometric ratio of the elements in the general chemical formula of the high electromechanical coupling coefficient lead-free piezoelectric ceramic material matrix, and obtaining a powder matrix after ball milling, drying, and sieving; (2) weighing a powder base material, a NaNbO3 template, a solvent, a plasticizer, a defoamer and a binder, and mixing them by roller milling to obtain a casting slurry; (3) casting, drying, cutting, laminating, baking, cold isostatic pressing, punching and debinding the casting slurry to obtain a ceramic green body; (4) sintering the ceramic green body and processing the finished product into a round piece with a diameter of 16 mm and a thickness of 0.7 mm to obtain a lead-free piezoelectric ceramic material ceramic piece; (5) coating the lead-free piezoelectric ceramic material ceramic sheet obtained in step (4) with silver paste and sintering the ceramic sheet to obtain a piezoelectric ceramic with a silver electrode; (6) polarizing the piezoelectric ceramic with silver electrodes obtained in step (5) to obtain a lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient; The solvent in step (2) is a mixture of butyl acetate and anhydrous ethanol in a mass ratio of 1:(0.8-1.2), the plasticizer is dioctyl phthalate, the defoamer is n-butanol, and the binder is polyvinyl butyral; the mass ratio of the powder base material, NaNbO3 template, solvent, plasticizer, defoamer and binder is 10:0.3:9:0.3:0.25:0.9; and the mixing time is 10-12 hours.
2. The lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient according to claim 1, characterized in that: During the casting in step (3), the scraper height is 100-200 μm.
3. The lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient according to claim 1, characterized in that: The baking condition in step (3) is to increase the room temperature to 100° C. and then keep the temperature for 30-60 minutes.
4. The lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient according to claim 1, characterized in that: The debinding conditions in step (3) are as follows: heating to 180°C at a rate of 0.5°C / min, keeping the temperature for 6 hours, then heating to 570°C at a rate of 0.2°C / min, keeping the temperature for 4 hours, and then cooling with the furnace.
5. The lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient according to claim 1, characterized in that: The sintering conditions in step (4) are as follows: using the buried firing method, the four-component disc is heated from room temperature to 900°C at a rate of 5°C / min, then heated to 1190°C at a rate of 3°C / min, kept at that temperature for 1 minute, cooled to 1110°C at a rate of 10°C / min, kept at that temperature for 6 hours, and then cooled with the furnace.
6. The lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient according to claim 1, characterized in that: In the step (6), the polarization temperature is 25-60° C., the polarization electric field is 15-20 kV / cm, and the polarization time is 20-30 min.
7. An application of the lead-free piezoelectric ceramic material with a high electromechanical coupling coefficient as claimed in claim 1, characterized in that: For use in energy harvesters, transducers or sensors.
Citation Information
Patent Citations
Lead-free potassium-sodium niobate-based textured piezoelectric ceramic with high-voltage electric energy collection performance and preparation method of lead-free potassium-sodium niobate-based textured piezoelectric ceramic
CN116715520A